Good Corporate Governance Memoderasi Capital Intensity, Capital Structure Terhadap Nilai Perusahaan - Nur Anita Chandra Putry; Dian Lestari Palambah; Putry, Nur Anita Chandra; Erawati, Teguh; Palambah, Dian Lestari (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2025)
The challenge of competition and the importance of firm value in the manufacturing industry. Examine the effect of Good Corporate Governance (GCG) as a moderation variable on intrinsic factors including capital intensity and capital structure. This purpose of this study is to investigate the capital intensity, capital structure on the firm value, good corporate governance as a moderating variable. The research examines was indexed manufacturing company in the Indonesian Stock Exchange, duration 2019-2023. The research is quantitative. The sample was identified through purposive sampling, with a total of 44 companies and 171 data observations from 5 years period. Multiple linear regression analysis, classical assumption test, hypothesis test, and residual test, was employed for data analysis, utilizing SPSS Statistic version 25. The results indicate that capital intensity did not affect, but capital structure have a significant positive impact on company valuation. GCG can strengthen the impact of capital intensity on firm values. GCG weakens capital structure on company values.